KESIAPAN GURU SD DALAM MENGINTEGRASIKAN STEAM KE DALAM PEMBELAJARAN TEMATIK - Abdul Rohim; Falina Siska; Haikal Alparizji; Tia Citra Bayuni (Elementary School and Education Journal, 2026)
This study aims to describe the readiness level of elementary school teachers in integrating the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach into thematic learning. The research employed a quantitative descriptive method with 15 elementary school teachers in Bekasi Regency who had attended STEAM-related training or teaching experience. The instrument used was a Likert-scale questionnaire covering three aspects of readiness: knowledge, attitude, and skills. The results showed that most teachers were categorized as ready in knowledge and attitude, but only moderately ready in skills, particularly in designing and implementing STEAM-based project learning. Factors influencing teacher readiness include training experience, school facilities, and access to digital learning resources. The study recommends continuous professional development and mentoring programs to enhance teachers’ capacity in implementing STEAM effectively within thematic learning at the elementary level.